Studying the foundations and identifying the signs of "ethical governance" in Farabi's political philosophy and civil science - R. Hoseinpour Tonekaboni; J. Masoudi (Taḥqīqāt-i Farhangī-i Īrān)
"Governance" is a new model and method in the field of politics and management, which has attracted the attention of many thinkers in the last few years. This model has many types, one of which is ethical governance. This governance, which insists on "management and administration" based on values, is a group action planned by the rulers and managers in order to implement a decent ethical system to integrate all business under a set and organization. Farabi is the first Iranian Muslim philosopher who, in addition to founding Islamic philosophy; has been the designer of many political and ethical discourse. In his political philosophy and civil science, he saw ethics and politics together, and the way to achieve the utopia of good fortune is only by converting to moral principles, which according to him, is possible through the cooperation and convergence of people and officials, and in the context of society. The subject of this article is the moral governance from the perspective of this peripatetic philosopher. The authors first defines governance and then ethical governance, then by adopting the method of content analysis and exploring Farabi's thoughts, they identify and introduce the foundations and signs of this governance/management model. Its purpose is to clarify the content of a percentage of Islamic philosophy in order to provide the content of one of the most important types of governance, for managers and officials of governmental and sub-governmental institutions, as well as citizens.